THE RELEVANCE OF THE WISDOM METHOD IN DA'WAH IN THE DIGITAL ERA - Widoyo, Agus Fatuh (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2025)
This study examines the concept of hikmah (wisdom) as a key method of da’wah (Islamic preaching) in Islam. The term hikmah appears in various contexts within the Qur'an, each carrying different meanings. Using a qualitative descriptive approach, this study explores the conceptual understanding and core values of hikmah in the practice of da’wah. The findings highlight that, first, hikmah is a foundational element in the da’wah method, as it integrates and complements various other approaches to preaching. Second, hikmah is frequently linked to gentleness and wisdom in the delivery of Islamic messages. This study also affirms that the essence of hikmah in da’wah lies in its alignment with the principles outlined in the Qur'an and Sunnah, which emphasize the importance of wisdom, contextual relevance, and effective communication in conveying Islamic teachings